Synthesis of Diflunisal Thiazolidinones as Anticancer Agents - ŞENER, AZİZE; ÖZSAVCI, DERYA; BİNGÖL ÖZAKPINAR, ÖZLEM; ŞENKARDEŞ, SEVİL; KÜÇÜKGÜZEL, ŞÜKRİYE GÜNİZ (BENTHAM SCIENCE PUBL LTD, 2016)
A series of diflunisal 4-thiazolidinones were synthesized. Some selected compounds were determined at one dose towards the full panel of 60 human cancer cell lines by National Cancer Institute. 2',4'-Difluoro-4-hydroxy-N-[4-oxo-2-(thiophen-2-yl)-1,3-thiazolidin-3-yl]biphenyl-3-carboxamide (4a) demonstrated the most marked effect on K-562 cancer cell line with 58.59 % growth inhibition at 10 mu M. Compound 4a was evaluated in vitro using the MTT colorimetric method against human leukemia cell line K-562 and mouse embryonic fibroblasts cell line NIH-3T3 at different doses for cell viability and growth inhibition. Compound 4a exhibited anticancer activity with IC50 value of 5.2 mu M against K-562 cells and did not display cytotoxicity towards NIH-3T3 cells compared with diflunisal. In addition, this compound could be an interesting prototype as an antiproliferative agent.
Keywords: Annexin-V; apoptosis; diflunisal; K-562 cancer cell line; 4-Thiazolidinone; NATIONAL-CANCER-INSTITUTE; HYDRAZIDE-HYDRAZONES; CASPASE ACTIVATION; DRUG DISCOVERY; APOPTOSIS; CYTOTOXICITY; DERIVATIVES; MECHANISMS; SCREEN; CELLS